Poly(Lactic Acid) Bionanocomposites Reinforced With Tempo-Oxidized Oil Palm Empty Fruit Bunch Nanocrystalline Cellulose - ., Eti Indarti (2017)
Bionanocomposites of poly(lactic acid) (PLA) and nanocrystalline cellulose (NCC) have the potentials to be used in various applications because of their biodegradability and renewability. However, due to their significant differences in hydrophobicity, it creates dispersibility and compatibility problems. To reduce these shortcomings, the NCC is modified via the silylation reaction using 3-aminopropyltriethoxysilane (APS). The NCC used in this research was isolated from unbleached OPEFB pulp using a combination of TEMPO oxidation and ultrasonic treatment, with solvent casting using chloroform employed for the preparation of the PLA-NCC bionanocomposite.